2017
DOI: 10.3389/fmicb.2017.02576
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Thiol-Disulfide Oxidoreductase DsbA Impairs cbb3-Type Cytochrome c Oxidase Biogenesis in Rhodobacter capsulatus

Abstract: The thiol-disulfide oxidoreductase DsbA carries out oxidative folding of extra-cytoplasmic proteins by catalyzing the formation of intramolecular disulfide bonds. It has an important role in various cellular functions, including cell division. The purple non-sulfur bacterium Rhodobacter capsulatus mutants lacking DsbA show severe temperature-sensitive and medium-dependent respiratory growth defects. In the presence of oxygen, at normal growth temperature (35°C), DsbA− mutants form colonies on minimal medium, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…This study aimed at probing the involvement of multiple DsbA proteins in bacterial CCM using S. oneidensis as the research model. Previous studies on bacteria with a single DsbA protein showed that these proteins play a critical role in the maturation of cyts c; its depletion reduces the abundance of the cyts c under examination by at least 50% (22) and impairs cbb 3 oxidase biogenesis (21). We anticipated that the loss of all DsbA proteins would bring S. oneidensis cells a great reduction in the overall abundance of cyts c. We were surprised when that turned out not to be the case.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This study aimed at probing the involvement of multiple DsbA proteins in bacterial CCM using S. oneidensis as the research model. Previous studies on bacteria with a single DsbA protein showed that these proteins play a critical role in the maturation of cyts c; its depletion reduces the abundance of the cyts c under examination by at least 50% (22) and impairs cbb 3 oxidase biogenesis (21). We anticipated that the loss of all DsbA proteins would bring S. oneidensis cells a great reduction in the overall abundance of cyts c. We were surprised when that turned out not to be the case.…”
Section: Discussionmentioning
confidence: 92%
“…However, it was later found that the loss of DsbA impairs but does not abolish CCM, whereas the essentiality of DsbD and DsbB remains the subject of debate (17)(18)(19)(20). In R. capsulatus, cyt c 2 and cyt cbb 3 oxidase (its structural subunits, CcoO and CcoP, are cyts c) are found to be produced at significantly reduced levels in DsbA-null mutants compared to those in the wild-type strain (21,22). In E. coli dsbA mutants grown under anaerobic conditions, the level of production of either their own cyts c (i.e., nitrate reductase small subunit NapB and cyt c 550 nitrite reductase NrfA) or foreign cyts c (i.e., NrfA and cd 1 nitrite reductase from Paracoccus denitrificans) decreases to 30 to 40% relative to that in the parental strains (20).…”
mentioning
confidence: 99%
“…Staining of the colonies was done as previously described 17 . The cbb 3 -Cox activities were measured by monitoring oxidation of reduced horse heart cyt c (Sigma Inc.) using chromatophore membranes according to 17,46 .…”
Section: Methodsmentioning
confidence: 99%
“…Yet, this hypothetical model suggests a link between the binding of Cu, ensuing conformation changes, and plausible thiol: disulfide oxidoreduction of CcoA. In this respect, the absence of R. capsulatus thiol: disulfide oxidoreductase DsbA (23), which catalyzes intramolecular disulfide bonds in extra-cytoplasmic proteins, is known to affect cbb 3 -Cox biogenesis (24). Whether or not DsbA is involved in these thiol: disulfide exchange reactions seen with CcoA is presently unknown, but future studies addressing determination of the thiol: disulfide exchange reaction rates (e.g., using 5,5-dithiobis-2-nitrobenzoic acid) ( 23) and the pKa values of appropriate thiols might identify the attacking and resolving Cys residues to further elucidate this process.…”
Section: Discussionmentioning
confidence: 99%